Pola Manajemen Sekolah Dalam Mewujudkan Sekolah Berpredikat Unggul : Studi Kasus Di Satit Phatnawitya School - Taufik, Irham; Mavianti, Mavianti (Al-Ulum: Jurnal Pendidikan Islam, 2024)
School management can be interpreted as everything related to the management of the educational process to achieve the goals that have been implemented, both short term, medium and long term goals. This research is intended to determine school management patterns at Satit Phatnawitya School Yala, Thailand. The research method uses descriptive qualitative methods with a case study approach. Data collection techniques through observation, documentation and interviews. Data sources were obtained from school principals, teachers and students. Data validity uses triangulation techniques, and data analysis uses interactive analysis through the steps of data collection, data reduction, data presentation, and verification or drawing conclusions. The research results show that Satit Phatnawitya School is a superior school both in terms of principal leadership, support from educators and education staff, facilities and infrastructure, as well as learning activities. School management focuses on these things which condition Satit Phatnawitya School to become a school with a superior predicate. This study concludes that the principal's leadership is the most important indicator in realizing a school with a superior rating.